Optical evaluation: the crux for effective management of colorectal neoplasia. (May 2020) - Shahidi, Neal; Vosko, Sergei; van Hattem, W. Arnout; Sidhu, Mayenaaz; Bourke, Michael J.
Advances in minimally invasive tissue resection techniques now allow for the majority of early colorectal neoplasia to be managed endoscopically. To optimize their respective risk–benefit profiles, and, therefore, appropriately select between endoscopic mucosal resection, endoscopic submucosal dissection, and surgery, the endoscopist must accurately predict the risk of submucosal invasive cancer and estimate depth of invasion. Herein, we discuss the evidence and our approach for optical evaluation of large (⩾ 20 mm) colorectal laterally spreading lesions.